Implementation of Wayang Sukuraga to Improve the Social Attitudes of Elementary School Students - Eneng Anisa; Iis Nurasiah; Din Azwar Uswatun (Jurnal Ilmiah Sekolah Dasar, 2022)
Wayang, as one of the traditional arts, is also a work of art that functions as a means of entertainment, education, and social media. This study aims to analyze the improvement of students' social attitudes in fifth-grade elementary school through the wayang sukuraga. This research design is a Classroom Action Research developed by Kemmis and Mc. Taggart with the implementation of research as much as 2 cycles. Subjects in this study amounted to 23 people. Data collection techniques were carried out using non-test techniques consisting of interviews, teacher activity observation sheets, student social attitudes observation sheets, field notes, and documentation of research activities. The data analysis technique was carried out descriptively. The results showed that the activities of educators in the first cycle obtained an average of 74 in the good category. In contrast, in the second cycle, they obtained an average of 88 in the good category. As for the social attitudes of students in the first cycle, the average result was 70% through the application of the puppet sukuraga in the fairly good category and then increased to 86% with the good category in the second cycle. Based on the results obtained, it can be concluded that the wayang sukuraga can improve the social attitudes of students in elementary schools.